Gizi Seimbang dari Dapur Nusantara : Edukasi dan Berbagi Bubur Manado di RT.01, Kelurahan Selumit - Nurul Hidayat; Gea Dilah Hermila; Muhammad Chaidir; Maria Deslianti Suryani Katim; Nanda Saputra; Noni Haironi; Sindy Arismawati Hasan; Yuniati Yuniati (Lembaga Pengembangan Kinerja Dosen, 2025)
The